Toribio Esquivel Obregón, encuentros y desencuentros con el antirreeleccionismo - Blanco, Mónica (El Colegio de México, A.C., 2010)
This paper analyzes the role of Toribio  Esquivel Obregón, lawyer and politician from Guanajuato, as one of the main figures of the antireelectionist movement in Mexico during 1909 and 1910. Francisco I. Madero  sought  to cooperate  with Toribio  Esquivel in order to organize a new political force, due to the recognition the guanajuatan gained after having published, in 1908, a strong criticism to the economic policy established by Porfirio Díaz’s regime. The paper examines the initial convergence  of interests between Toribio Esquivel and Francisco I. Madero, as well as the reasons why the relation  became difficult and ultimately  broke up. Esquivel’s political activism in his home state, as well as his position  against any transaction against the regime, deteriorated his relation with Madero. This study  of the rivalry between Esquivel and Madero allows us to deepen our knowledge of a largely unknown history:  that of the internal political struggle in the Antireelectionist Center of Mexico.